Advanced Solar Still Development: Improving Distilled Water Recovery and Purity via Graphene-Enhanced Surface Modifiers - Baticados, El Jirie N.; Capareda, Sergio C.; Liu, Shuhao; Akbulut, Mustafa (Frontiers in Environmental Science, 2020)
Solar distillation system depends on adhesion of water molecules inside the glass cover of solar stills. Regular glass surfaces are prone to adsorbing other unwanted compounds and in turn lowers the percentage of recovery of pure distilled water. In this study, the production of purified distilled water was compared with and without the use of graphene-based surface modifiers. In areas where salt content is high, the first pass is still usually laden with salts. Hence, to improve adhesion of water and rejection of salts, both the inside glass cover surfaces and the metal absorber plates were modified using oxygen plasma treatment and graphene surface enhancement. Results showed a 48.9% improvement of distilled water recovery from an initial recovery of 2.90 L/m2/day to an average of 4.32 L/m2/day. In addition, the resulting distilled water passes the World Health Organization (WHO) drinking water standards such as pH, electrical conductivity (EC) and salinity. The average reduction in electrical conductivity was 96.52%, an average increase of 5.06% of pH and an average reduction of salinity of 96.52%, all measured at the highest brine salinity of 5%. The reported value of electrical conductivity was 23.33 µS/cm, a lowest and near neutral pH of 6.85 and an average salinity of 12.10 ppm.